Analisis Rantai Pasok Udang Vaname (Litopenaeus vannamei) di Kabupaten Konawe Selatan - Nurmiati Nurmiati; Bahari Bahari; Rosmawaty Rosmawaty (Universitas Halu Oleo, 2022)
This research aims to (1) analyze track supply chain, (2) examine business processes and distribution patterns, and (3) analyze the marketing efficiency of vaname shrimp in South Konawe Regency. The population in this research is the owner cultivators in the shrimp farming unit. The sampling technique in this research was carried out in two stages, namely a sample of cultivators and a sample of traders, carried out using the cluster random sampling method. The data collected in this research include primary data and secondary data. The dat analysis done in a descriptive and quantitative. The results of this research indicate that there are 3 supply chain consists of vaname shrimp, track I (breeders - cultivators - retailers - consumers), track II (breeders - cultivators - village collectors - fishery companies - consumers) and track III (seeders - cultivators - traders). village collectors - retailers - consumers). The vaname shrimp supply chain business process has not been well integrated. The market information received is not yet known publicly both regarding price and quantity. The vaname shrimp supply chain in which there are 3 types of flows, product flow, financial flow and information flow flowing from upstream to downstream and downstream to upstream. The performance of the vaname shrimp supply chain has been efficient with the average share indicator or share of the price received by farmers in all lines of 85.63%. The average trader profitability value from all lines is 1.06.Keywords: Vaname Shrimp, Supply Chain, Business Pattern, Distribution Pattern, Marketing Efficiency